Sustainability of street furniture design in urban Malaysia - Aziz, Arnis (2013)
Today, urban spaces are one of the major elements that define the city‟s unique and attractive points. Although comparatively small in scale, street furniture is an element that can play an essential role in developing the quality of urban spaces and add value in representing city identity. Street furniture refers to the objects or facilities that provide various services and functions to the public in the area of urban public spaces. It is a structural element of environment that normally varies depending on the social and cultural features of a city or a country. It helps in contributing to human activities and to surrounding. This research seeks study is to implement the criteria of sustainable design in street furniture. Thus, in this research it is imperative that the sustainable criteria for street furniture design in Malaysia should be assessed. In providing a comprehensive data and background information, a literature search and document analysis was done. The major findings of this research proposed sustainable design criteria based on the literature search and document analysis. This was used to measure each sets of the data collection gathered. Furthermore, interviews with professionals formed part of the author‟s in depth method. Data collection of these methods was analysed via the qualitative approach. Links were made between the sustainable street furniture design practised in Malaysia and the practised experiences in the other countries. The question of what is roles street furniture plays and what sustainable design is, are discussed. The criteria for sustainable design were examined and sustainability issues and problems of street furniture design in Malaysia were also analysed. Finally, the study explored the importance and possibilities of adopting sustainable design criteria for street furniture in Malaysia. It is hoped that this study will contribute towards creating awareness of the importance of sustainable design in street furniture in the country which in turn will help in the sustainable development of the urban areas and cities, besides improving the environment and urban living.